A Bio‐Based Supramolecular Adhesive: Ultra‐High Adhesion Strengths at both Ambient and Cryogenic Temperatures and Excellent Multi‐Reusability. Issue 28 (9th August 2022) - Sun, Peng; Mei, Shan; Xu, Jiang‐Fei; Zhang, Xi
Abstract: Developing high‐performance and reusable adhesives from renewable feedstocks is of significance to sustainable development, yet it still remains a formidable task. Herein, castor oil, melevodopa, and iron ions are used as building blocks to construct a novel bio‐based supramolecular adhesive (BSA) with outstanding adhesion performances. It is prepared through partial coordination between melevodopa functionalized castor oil and Fe 3+ ions. Noncovalent interactions between adherends and the catechol unit from melevodopa contribute to reinforcing adhesion, and the metal‐ligand coordination between catechol and Fe 3+ ions is utilized to strengthen cohesion. By combining strong adhesion and tough cohesion, the prepared BSA achieves an adhesion strength of 14.6 MPa at ambient temperature, a record‐high value among reported bio‐based adhesives as well as supramolecular adhesives to the best of knowledge. It also outperforms those adhesives at cryogenic temperature, realizing another record‐high adhesion strength of 9.5 MPa at −196 °C. In addition, the BSA displays excellent multi‐reusability with more than 87% of the original adhesion strength remaining even after reuse for ten times. It is highly anticipated that this line of research will provide a new insight into designing bio‐based adhesives with outstanding adhesion performances and excellent multi‐reusability. Abstract : An ultra‐strong and multi‐reusable bio‐based adhesive is successfully constructed by utilizing castor oil, melevodopa, and iron ions as building blocks. By combining strong adhesion with tough cohesion, it achieves record‐high adhesion strengths of 14.6 MPa at ambient temperature and 9.5 MPa at −196 °C. What's more, it exhibits excellent multi‐reusability of ten times with over 87% adhesion strength remaining.